(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The formulation of the research problem : 1) how is Widyaiswara’s readiness to use learning technology? 2) How is Widyaiswara’s learning innovation using learning media with multimedia technology? This study uses a qualitative descriptive method. The researcher is the key instrument, the data grouping technique is triangulated, the data analysis is inductive, and the results of qualitative research emphasize real reality rather than reasoning. The results show: to use Widyaiswara learning technology, it can be developed with Community learning or Community of Practice, discussions among Widyaiswaras in the context of the transfer of skills process. among Widyaiswara. To improve the specifications of learning technology owned by Widyaiswara, it is necessary to support the institution for facilities and infrastructure that are in accordance with learning technology standards. Widyaiswara is expected to have competency standards in using learning technology, to support this, various activities and activities are needed. In order to certify the training staff so that they can be recognized and guaranteed the learning implementation process that they carry out. Given the very varied pattern of recruitment of Widyaiswara at BPSDM Riau Province, it is necessary to build character as functional staff who have the main tasks and functions of Dikjartih, evaluation and development so that they are expected to be able to carry out personal branding or individual capacity building that can support motivation to be more advanced and professional.